1992
DOI: 10.1128/aac.36.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Comparative kill and growth rates determined with cefdinir and cefaclor and with Streptococcus pneumoniae and beta-lactamase-producing Haemophilus influenzae

Abstract: The relationship between the growth rate and the kill rate was used to evaluate and to compare the in vitro bactericidal activities of cefdinir, a new oral cephalosporin, and cefaclor against Streptococcus pneumoniae and ,-lactamase-producing strains of Haemophilus influenzae. These frequently encountered pathogens of community-acquired respiratory tract infections are usually susceptible to both drugs. The MIC ranges for cefdinir and cefaclor were, respectively, 0.03 to 0.06 and 0.25 to 0.5 ,ug/ml for S. pneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Yourassowsky and coworkers (27,28) have reported rapid killing rates for cefdinir and cefaclor against penicillin-susceptible pneumococci. Jacobs et al (15) have reported a paradoxical increase in viability count for four of eight strains tested with ciprofloxacin and with temafloxacin for two of eight strains tested.…”
Section: Discussionmentioning
confidence: 99%
“…Yourassowsky and coworkers (27,28) have reported rapid killing rates for cefdinir and cefaclor against penicillin-susceptible pneumococci. Jacobs et al (15) have reported a paradoxical increase in viability count for four of eight strains tested with ciprofloxacin and with temafloxacin for two of eight strains tested.…”
Section: Discussionmentioning
confidence: 99%